Exogenous Ergothioneine and Glutathione Limit Postharvest Senescence of Arugula - Dhanya Sivakumar; Gale Bozzo (MDPI AG, 2024)
Arugula is susceptible to postharvest deterioration. We tested the impact of exogenous antioxidant (i.e., ergothioneine and glutathione) dip solutions on arugula quality during storage at 4 °C or 10 °C for up to 17 days relative to a non-antioxidant treatment. Leaves from each dip treatment and storage temperature were assessed for visual quality and endogenous antioxidant metabolite profiles. Overall, leaf discolouration, wilting, and decay were more rapid at 10 °C than at 4 °C. Both antioxidant treatments limited leaf discolouration at 4 °C. Exogenous ergothioneine reduced wilting at 4 °C, whereas exogenous glutathione limited the incidence of leaf decay. At 10 °C, glutathione reduced the incidence of discolouration and decay, whereas both antioxidant dip treatments limited the decline in leaf yellowing. Ergothioneine was solely detected in ergothioneine-treated leaves; a decrease occurred within the first two days of storage but was unchanged thereafter. Although both antioxidant treatments did not affect endogenous glutathione concentrations at either storage temperature, glutathione disulfide was stable within the glutathione-treated leaves, whereas it increased in the other treatments. Ascorbate degradation was delayed in ergothioneine-treated leaves at 4 °C relative to all other treatments, whereas both antioxidant treatments little affected ascorbate metabolism in leaves stored at 10 °C.